Prova judiciária e verdade: enfoque constitucional - Vilar Filho, José Eduardo de Melo (2006)
The judicial evidence and the search for the truth in court are analyzed under the perspective of the constitutional standards of judicial procedure. At first, the constitutional norms related to evidence are identified, establishing its nature and its way of application. Following, it is analyzed the relationship between the judicial process and the truth. It is, then, compared the constitutional standards and the legal framework of judicial evidence, concerning its most important aspects, such as: the object and the evaluation of the evidence, the judge initiative in the production of evidence the burden of proof, the evidence required to grant provisional injunctions, legal limits about the production of evidence (legally imposed evidences and prohibition of producing evidence by illegal means), the usefulness of evidence produced in other procedures and, at last, the legal effects of the defendant’s absence as regards to evidence